FUNCTIONAL FOODS AS ADJUNCTIVE THERAPY IN THE MANAGEMENT OF CHRONIC DISEASES: A PHARMACOLOGICAL PERSPECTIVE (International Journal of Food and Nutritional Sciences, 2022)
Abstract: Functional foods, which offer benefits beyond basic nutrition, are increasingly recognized for their potential as adjunctive therapies in managing chronic diseases. This research paper explores the pharmacological perspectives on integrating functional foods into conventional treatment paradigms for chronic conditions such as cardiovascular disease, diabetes, cancer, and neurodegenerative disorders. By analyzing current clinical studies and pharmacological mechanisms, this paper aims to elucidate how functional foods can complement traditional therapeutic approaches to enhance disease management and patient outcomes. Functional foods, including but not limited to, omega-3 fatty acids, antioxidants, and fiber-rich foods, have demonstrated varied efficacy in modulating disease processes through biochemical pathways. This paper reviews the evidence supporting the role of these foods in mitigating disease progression, reducing side effects of conventional medications, and improving overall health. Emphasis is placed on the interaction between functional foods and drug therapies, highlighting both synergistic effects and potential contraindications.Additionally, this study discusses the mechanisms through which functional foods exert their therapeutic effects, such as anti-inflammatory, antioxidant, and metabolic modulation. The integration of functional foods into clinical practice presents challenges related to standardization, dosing, and patient adherence. Thus, the paper also addresses these challenges and proposes strategies for overcoming them to optimize the use of functional foods in chronic disease management.Overall, this research underscores the importance of a multidisciplinary approach combining pharmacology, nutrition science, and clinical practice to harness the full potential of functional foods as adjunctive therapies. The findings suggest that with proper integration and clinical validation, functional foods could play a significant role in enhancing the management of chronic diseases.